SOSIALISASI LITERASI PRODUCT QUALITY BERAS ORGANIK DI RPTRA KELURAHAN PAPANGGO KECAMATAN TANJUNG PRIOK JAKARTA UTARA - Harianja, Elma Sari Serepina; Zalukhu, Meschadin Bri Iman; Hidayat, Koerniawan (Jurnal Abdimas Bina Bangsa, 2025)
Organic rice is a type of rice that is grown without the use of pesticides herbicides, or other synthetic chemicals. The growing process prioritizes environmental sustainability and soil health, using environmentally friendly farming methods and prioritizing ecosystem balance. Organic rice has a more natural flavor and better texture compared to regular (non-organic) rice. In addition, consumption of organic rice is believed to be healthier because it is free from chemicals that can harm the body's health. This product is suitable for consumers who care about personal health, sustainability and the environmental impact of the products they consume.